2007
DOI: 10.2174/187152007780058669
|View full text |Cite
|
Sign up to set email alerts
|

Acridine and Acridone Derivatives, Anticancer Properties and Synthetic Methods: Where Are We Now?

Abstract: Acridine derivatives are interesting chemotherapeutic agents that were first used as antibacterial and antiparasite agents. In this review we wish to concentrate our attention on the anticancer properties of acridines used in clinics since the 1970's. Based on recent results, an outlook on antitumour acridine chemotherapy will be proposed. The biological activity of acridines is mainly attributed to the planarity of these aromatic structures, which can intercalate within the double-stranded DNA structure, thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(102 citation statements)
references
References 0 publications
1
98
1
2
Order By: Relevance
“…C-1311 and other acridine-based compounds display nuclear and perinuclear accumulation and exert their cytotoxic activity via direct interaction with DNA as well as with DNA-modifying enzymes including topoisomerase I or II (Topcu, 2001;Belmont et al, 2007). To exclude the possibility that differential subcellular accumulation of IAs is the basis of the observed difference in cytotoxicity and cellular fluorescence, A549/K1.5 cells were incubated with 10 M concentrations of selected IAs from groups A and B in the presence or absence of FTC and subjected to fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…C-1311 and other acridine-based compounds display nuclear and perinuclear accumulation and exert their cytotoxic activity via direct interaction with DNA as well as with DNA-modifying enzymes including topoisomerase I or II (Topcu, 2001;Belmont et al, 2007). To exclude the possibility that differential subcellular accumulation of IAs is the basis of the observed difference in cytotoxicity and cellular fluorescence, A549/K1.5 cells were incubated with 10 M concentrations of selected IAs from groups A and B in the presence or absence of FTC and subjected to fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 In a more recent study, it has been reported that quadruplex-binding trisubstituted acridines have exhibited rapid anti-tumor effects involving several parallel mechanisms, including telomere uncapping, direct or indirect telomerase inhibition with the characteristic induction of senescence and apoptosis. [3][4][5][6][7][8] Recent research has also shown that G-quadruplexes selectively target both telomerase and telomere in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Acridine and related derivatives are potent DNA-intercalating anticancer agents. [16,17] Recently, Sedlacek et al have demonstrated pH-controlled activation of polymer-conjugated acridine-based anticancer drugs in cancer cells. [17] This was possible because acridine exists in water in two prototropic forms (pK a % 5.3), [14,18] one being neutral (Ac) and the second being protonated (AcH + , cf.…”
Section: Introductionmentioning
confidence: 99%